2016
DOI: 10.3892/br.2016.620
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: Novel regulatory molecules in acute lung injury/acute respiratory distress syndrome

Abstract: Abstract. Acute lung injury (ALI) and the more severe acute respiratory distress syndrome (ARDS) are common and complex inflammatory lung diseases. MicroRNAs (miRNAs), a type of non-coding RNA molecule that regulate gene expression at the post-transcriptional level, have emerged as a novel class of gene regulators, which have critical roles in a wide range of human disorders and diseases, including ALI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 41 publications
3
41
0
Order By: Relevance
“…According to existing research, an obvious reduction of miR‐27b has been observed in several NSCLC cell lines, and the forced overexpression of miR‐27 could suppress cell proliferation and invasion of NSCLC (J. Jiang et al, ). The experimental data of other study is in consistency with our findings, thereby supporting that miR‐27b was upregulated in ALI and deregulated miR‐27b is beneficial to ALI (Cao, Lyu, Tang, & Li, ).…”
Section: Discussionsupporting
confidence: 91%
“…According to existing research, an obvious reduction of miR‐27b has been observed in several NSCLC cell lines, and the forced overexpression of miR‐27 could suppress cell proliferation and invasion of NSCLC (J. Jiang et al, ). The experimental data of other study is in consistency with our findings, thereby supporting that miR‐27b was upregulated in ALI and deregulated miR‐27b is beneficial to ALI (Cao, Lyu, Tang, & Li, ).…”
Section: Discussionsupporting
confidence: 91%
“…Acute lung injury or ALI is a traumatic disease which maybe caused by several direct (shock, severe sepsis, pulmonary contusion, gastroesophageal reflux, pneumonia, drug toxicity, transfusion, and acute pancreatitis) or indirect factors like ventilator induced or mechanical injury etc (Cao et al, 2016). The peculiar characteristics of ALI are enhanced permeability of capillary endothelial and alveolar epithelial cells, scattered pulmonary alveolar and interstitial edema, progressive and refractory hypoxemia and impaired gas exchange all of which expedite arterial hypoxemia,ultimately leading to respiratory failure (Zeng et al, 2013;Tamarapu Parthasarathy et al, 2012;Xie et al, 2012;Cai et al, 2012a;Agarwal et al, 2006).…”
Section: Macrophages In Acute Lung Injurymentioning
confidence: 99%
“…The macrophages are important mediator in both acute and chronic inflammation [15], here we selected this population of immune cells for further investigations. As miRNAs have been reported to serve as novel therapeutic targets in acute lung injury and ARDS [13], we adopted the strategy of miRNA microarray to interrogate the expression profile in ARDS-related inflammatory setting. The comparative study has identified multiple differentially expressed candidate miRNAs in ARDS vs control groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its normal functions, assembling evidences suggest that miRNA are also involved in various pathological conditions such as cardiomyopathies [8], atherosclerosis [9], obesity [10] and cancer [11]. Most importantly, emerging evidences suggest that miRNAs play crucial roles in inflammation responses [12], as well as in acute lung injury and ARDS [13]. …”
Section: Introductionmentioning
confidence: 99%